Structural asymmetries at the roots of the eurozone crisis: what’s new for industrial policy in the EU? - Botta, Alberto (PSL Quarterly Review, 2014)
In this paper, we analyze and try to measure productive and technological asymmetries between central and peripheral economies in the eurozone. We assess the effects such asymmetries would likely bring about on center–periphery divergence/convergence patterns, and derive some implications as to the design of future industrial policy at the European level. We stress that future European Union (EU) industrial policy should be regionally focused and specifically target structural changes in the periphery as the main way to favor center–periphery convergence and avoid the reappearance of past external imbalances. To this end, a wide battery of industrial policy tools should be considered ranging from subsidies and fiscal incentives to innovative firms, public financing of R&D efforts, sectoral policies, and public procurements for home-produced goods. All in all, future EU industrial policy should be much more interventionist than it currently is, and dispose of much larger funds with respect to the present setting in order to effectively pursue both short-run stabilization and long-run development goals. Keywords: Center–Periphery Structural Symmetries, EU Industrial Policy JEL Codes: E12, F15, O25, O52